Florence Nightingale's legacy on the role of men in community nursing. (2nd June 2021) - Harrison, Thomas
Abstract : Florence Nightingale is credited with reforming the profession of nursing, and her teachings allowed nursing to be perceived as an almost exclusively female career. However, the long history of men's role in nursing before Nightingale is frequently ignored. Males currently account for one in ten UK nurses, with that figure even less in community nursing, and the ones present receive differential treatment when it comes to hiring and promotion, career opportunities, and stigma associated with gender perceptions. This article attempts to gain a better understanding of the problems that face workforce planning with regards to the lack of men in community nursing.